Human papillomavirus as an independent risk factor of invasive cervical and endometrial carcinomas in Jordan - Mohammad A. Abu-Lubad; Dua'a A. Jarajreh; Ghada F. Helaly; Hamed M. Alzoubi; Weliam J. Haddadin; Mahmoud D. Dabobash; Eman M. Albataineh; Amin A. Aqel; Nedal A. Alnawaiseh (Elsevier, 2020)
Background: Endometrial and cervical carcinomas are the most common gynecologic malignancies in Western world and many countries. The human papillomavirus (HPV) high-risk genotypes are associated with cervical carcinoma (CC). Chlamydia trachomatis (C. trachomatis), the most common sexually transmitted bacterial infection worldwide, considered a cofactor for HPV infection and CC. Information on HPV infection rate and type distribution among Jordanian women having CC is currently limited and unavailable among those with endometrial carcinoma. Therefore, the present study aimed to provide an updated estimate on HPV infection rate and its high-risk genotypes' distribution among Jordanian women by comparing data from invasive cervical carcinoma (ICC) to normal cervical tissues. Similarly, assessment of HPV infection rate was extended to the endometrial tissues. C. trachomatis infection was investigated as well to explore its possibility as HPV cofactor for induction of such carcinomas. Methods: Total DNA was extracted from 144 formaldehyde-fixed paraffin-embedded cervical and endometrial tissue, equally divided between age-matched control and carcinoma cases. Polymerase chain reaction (PCR) was used for general detection of HPV-DNA, high risk HPV-16 and 18 genotypes and C. trachomatis DNA using specific primers. Results: HPV infection was detected in 91.7% and 61.1% of cervical cancer patients and controls, respectively. Likewise, it was higher among cases (47.2%) than controls (13.8%) in endometrial biopsies. Significantly higher HPV infection rates were found among ICC and endometrial control biopsies of women >50 years. Out of 33 HPV positive ICC cases, single HPV-16 infections were detected in 69.7% compared to HPV-18 (15.2%), while HPV-16/18 co-infections were only found in three (9%) samples. C. trachomatis was not detected in all studied groups. Conclusion: The present study has successfully provided an updated estimate on HPV infection rate among Jordanian women with and without ICC and endometrial carcinoma. In addition, a lack of co-infection was observed between HPV and C. trachomatis in both cancer types. Keywords: Human papillomavirus, Invasive cervical carcinoma, Endometrial carcinoma, Chlamydia trachomatis